Reflective approaches in medical education. Implications on medical imaging. - Raja Azhar, Raja Farahhana; Mohd Yusoff, Mohamed Nadzri; Zainuddin, Zainul Ibrahim (NOVA Southeastern university, 2018)
Purpose: This paper reviewed literature regarding the utility and direction of reflective approaches in Medical imaging education. Methods: The Scopus database was accessed. The word “Reflective” was used as the main search term to look for the relevant literature. The inclusion criteria used in this study comprised of those papers published in English between the years 2006 to 2016, indexed in Scopus database, and limited to those discussing the topic on reflective approaches in medical education. Published papers that have the main search terms in the articles’ title only were tabulated.The data were then filtered using other Reflective related terms.Thematic analysis was done. Results: Two hundred and four articles were identified to have one or more search terms in the articles’ titles only. Studying the data using other reflective related terms revealed that the term “Reflective Writing” contributed the highest frequency, followed by “Reflective Journal” and “Reflective Learning”. Twenty- four studies evaluated students' reflective approaches in assessing and improving the domain of professionalism in Medical sciences. Twenty-two studies showed the researchers utilized various types of reflective approaches for evidence of students learning skills. Other studies noted the efficacy of different types of reflective learning in the domains of attitude, teamwork, empathy, learning skill, competencies, clinical skill and patient care. Pertinent to Medical imaging education area, only two studies were found; one reported the promotion of reflective learning while the other touched on the portfolio. Conclusion: This review, based on Scopus database, depicts the educational approaches that made use of the concept of reflection. They are used to facilitate the learning and assessment in various medical disciplines. There is a dearth of articles that address reflective approaches in relation to Medical imaging education. Much work is required to understand how reflective approaches can be used to effectively assess the students’ performances in various domains in Medical imaging education.